The effect of extended continuous nursing strategy applied to patients with mild brain injury on their quality of life and self-efficacy - Zhang, Li; Ma, Yanmei; Liu, Jia; Cai, Miao; Zheng, Wenqiu (Frontiers in Surgery, 2022)
Objective To analyze the effect of extended continuous nursing strategy applied to mild brain injury patients on their quality of life and self-efficacy level. Methods from September 2018 to November 2019, 120 patients with mild brain injury were treated in our hospital. With the help of the digital table as the grouping basis, the subjects satisfying the inclusion conditions were named as the study group and the control group, 60 in each group. Among them, the control group carried out traditional nursing, and the research group carried out extended continuous nursing. Before intervention and at the end of the 4th week after intervention, the patients in the two groups received quality of life scale and self-efficacy questionnaire. Results after intervention, the SF-36 quality of life scale scores in the study group were higher than those in the control group, the difference was statistically significant (P < 0.05). After intervention, the scores of basic knowledge of disease, harmful cognition of adverse factors, treatment knowledge, self-management knowledge and prevention knowledge of complications in the study group were higher than those in the control group (P < 0.05). Conclusion the application of Hospital Extension continuous nursing strategy in patients with mild brain injury can improve their self-efficacy level, and improve their quality of life and nursing satisfaction, which is worthy of further promotion in clinical practice.